Group selfies and Snapchat: From sociality to synthetic collectivisation. (April 2019) - Page, Ruth
Highlights: The paper sets out synthetic collectivisation as a new discursive strategy. Perspective in video-sharing is created through visual, aural and verbal resources. There are three types of intersubjectivity: zero, presented and indirect. The Featured Stories of Snapchat favour group selfies and quasi selfies. The construction of large scale sociality in group selfies is ideologically loaded. Abstract: This paper sets out a multimodal framework that can be used to explore the ways in which people are positioned as individuals and groups within the selfies and other kinds of representations found in video-sharing practices. Unlike earlier, monomodal accounts of selfies, the framework accounts for the visual, aural and verbal resources that are used in video-sharing. The analysis focuses on the videos and photos that are produced and consumed in the Featured Stories of Snapchat as collective accounts of public events of different kinds. The results show that, in Snapchat, constructing group identities is prominent, both in selfies and quasi-selfies. This reflects a discourse of 'us-ness' current in many forms of social media, and which prizes particular forms of sociality. The uses of this discourse are ideologically charged, and include the strategic use of synthetic collectivisation as an emerging form of audio-visual communication which contrives to position the individual member of the audience as if they were part of a larger group, sharing the same experience and perspective as the person creating the video. The framework is used in this paper to examine the ways in which the collective identities of fans, mourners and protestors are constructed in Featured Stories from Snapchat, but is of relevance to many other forms of multimodal communication that are shared through social media sites and services.